Validation of a Dynamic Measure of Current Cognitive Reserve in a Longitudinally Assessed Sample of Healthy Older Adults: The Tasmanian Healthy Brain Project. (June 2019) - Summers, Mathew J.; Thow, Megan E.; Ward, David D.; Saunders, Nichole L.; Klekociuk, Shannon Z.; Imlach, Abbie-Rose; Summers, Jeffery J.; Vickers, James C.
Cognitive reserve (CR) is a theoretical construct describing the underlying cognitive capacity of an individual that confers differential levels of resistance to, and recovery from, brain injuries of various types. To date, estimates of an individual's level of CR have been based on single proxy measures that are retrospective and static in nature. To develop a measure of dynamic change in CR across a lifetime, we previously identified a latent factor, derived from an exploratory factor analysis of a large sample of healthy older adults, as current CR (cCR). In the present study, we examined the longitudinal results of a sample of 272 older adults enrolled in the Tasmanian Healthy Brain Project. Using results from 12-month and 24-month reassessments, we examined the longitudinal validity of the cCR factor using confirmatory factor analyses. The results of these analyses indicate that the cCR factor structure is longitudinally stable. These results, in conjunction with recent results from our group demonstrating dynamic increases in cCR over time in older adults undertaking further education, lend weight to this cCR measure being a valid estimate of dynamic change in CR over time.